Sustainable Investments: A New Model for Post-Pandemic Economic Recovery - Cindy Sandra Lumingkewas; Lilis Sulastri; Kadar Nurjaman; Martanto; Windy Dermawan (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This study analyzes the impact of sustainable investment on economic indicators by considering five main banks in Indonesia, namely PT Bank BRI (BBRI), Bank UOB Indonesia (UOYB), PT Bank Central Asia Tbk (BBCA), PT Bank Negara Indonesia Tbk (BBNI), and PT Bank BJB Tbk. (BJBR). Statistical data involving economic growth, unemployment rates, greenhouse gas emissions, and increasing added value in local communities are analyzed. The results show that sustainable investment provides a significant positive impact, creating sustainable economic growth, reducing unemployment rates, improving the welfare of local communities, and reducing environmental impacts by reducing greenhouse gas emissions. The broader implications emphasize the importance of integrating sustainability in economic policy to achieve inclusive and sustainable growth.